IMPLEMENTASI METODE SHOW AND TELL DALAM MENINGKATKAN KETERAMPILAN BERBICARA PADA PESERTA DIDIK KELAS V DALAM PEMBELAJARAN BAHASA INDONESIA - Fauziah, Inayatul (Universitas Muria Kudus, 2025)
This research aims to test the effectiveness of the show and tell learning method in improving students' speaking skills, especially grade 5 students at SDN 01 Larangan. The show and tell method involves the activity of showing something to the audience (students) and explaining, describing, or telling stories about things that are relevant to the object being shown. Conventional methods, especially in learning speaking skills such as telling stories in front of the class, often cause students to feel less confident, embarrassed and unprepared. This research focuses on finding out whether the application of the show and tell method can improve the speaking skills of grade 5 students at SDN Larangan 01, Larangan Village, Larangan District, Brebes Regency. The results of the research show that applying the show and tell method in learning Indonesian has been proven to improve the speaking skills of grade 5 students.